Adult Learner Experiences of an Accelerated Degree Program - Carol Kasworm (Adult Education Research Conference, 2001)
This qualitative case study explored the experiences of adult learners in an undergraduate accelerated degree program. Key beliefs of the experience focused upon four themes: 1) the adult degree program as a supportive world, 2) fellow students as a family, 3) successful adult students are dedicated, and 4) the paradoxical involvement in learning in an accelerated program.